Availability and Use of Information and Communication Schools In Delhi - Siddiqui, M.A.; Abraham, Jessy; Khan, Mohsin Ali (INDIAN EDUCATIONAL REVIEW, 2009)
The present study intended to study the availability and use of information and communication technology (ICT) in schools in Delhi. Since the government and private initiatives are increasing and attempts are made towards integration of technology in school education, a study about the availability and use of computers covering the teachers as well as students was taken up.